PHENOMENOLOGICAL STUDY OF COMMUNICATION EXPERIENCE AS A MEDIUM OF CULTURAL ADAPTATION FOR FOREIGN NATIONALS AT EASTON PARK APARTMENT - Nurul Huda; Engkus Kuswarno; Ilham Gemiharto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research examines communication experiences of foreign nationals as a medium of cultural adaptation at Easton Park Apartment Jatinangor, a local residential facility not designed for international communities. Employing Alfred Schutz's social phenomenology approach emphasizing subjective meaning construction within the everyday lifeworld, data were collected through in-depth interviews with six informants from England, Kenya, Ethiopia, Pakistan, China, and Bangladesh, complemented by observation and documentation. Data analysis followed Creswell's phenomenological stages including horizontalization, theme formation, textural-structural description, and identification of experience essence. Findings reveal that awareness of differences emerges through language barriers, communication style variations, and unfamiliar social norms, which informants interpret as challenges triggering active learning through translation technology, smiles as universal language, independent Indonesian language learning, and participation in local cultural practices. Indonesian hospitality serves as a crucial factor reducing alienation, while mutual understanding occurs through gradual meaning negotiation. Intersubjectivity primarily forms in spaces such as mosques, churches, markets, and food stalls rather than within apartments whose individualistic structure inhibits spontaneous interaction.